2016
DOI: 10.1158/2159-8290.cd-15-0827
|View full text |Cite|
|
Sign up to set email alerts
|

Bruton Tyrosine Kinase–Dependent Immune Cell Cross-talk Drives Pancreas Cancer

Abstract: Pancreas ductal adenocarcinoma (PDAC) has one of the worst five-year survival rates of all solid tumors, and thus new treatment strategies are urgently needed. Here we report that targeting Bruton’s Tyrosine Kinase (BTK), a key B cell and macrophage kinase, restores T cell-dependent anti-tumor immune responses, thereby inhibiting PDAC growth and improving responsiveness to standard-of-care chemotherapy (CTX). We report that PDAC tumor growth depends on crosstalk between B cells and FcRγ+ tumor-associated macro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
372
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(394 citation statements)
references
References 49 publications
20
372
1
1
Order By: Relevance
“…Previous work from our group and others demonstrated in vivo Th1 skewing (21,22) with ibrutinib treatment in murine models. Here, we observed no significant changes in the percentage of T cells expressing intracellular Th1 (IFN-γ) or Th2 (IL-4) cytokines in CLL patients treated with ibrutinib.…”
Section: Ibrutinib Downregulates Immunosuppressive Molecules Cd200mentioning
confidence: 73%
See 1 more Smart Citation
“…Previous work from our group and others demonstrated in vivo Th1 skewing (21,22) with ibrutinib treatment in murine models. Here, we observed no significant changes in the percentage of T cells expressing intracellular Th1 (IFN-γ) or Th2 (IL-4) cytokines in CLL patients treated with ibrutinib.…”
Section: Ibrutinib Downregulates Immunosuppressive Molecules Cd200mentioning
confidence: 73%
“…In a CLL mouse model of bacterial infection, ibrutinib treatment led to a more than 2-fold increase in expansion of Th1 pathogen-specific T cells and corresponding suppression of Th2 immunity (21). Ibrutinib treatment also leads to a shift in macrophages toward a Th1-supportive phenotype and increases CD8 + T cell tumor infiltration in a mouse model of pancreatic cancer (22).…”
Section: Ibrutinib Treatment Increases Numbers Of Both Cd4mentioning
confidence: 99%
“…Interestingly, recent work in Kras-driven PDAC GEMMs has shown that depletion of tumor stroma or targeting Cxcl12 from tumor-associated fibroblasts exhibits a synergistic effect with immune checkpoint therapies (Feig et al 2013;Ozdemir et al 2014), suggesting that conditioning of the PDAC stroma might be a prerequisite for attaining therapeutic responses to immunotherapies. In addition, stroma-derived Cxcl13 has been shown to induce the infiltration of B-cell subpopulations and promote tumor growth, likely through programming TAMs toward an M2 phenotype (Gunderson et al 2015;Lee et al 2015;Pylayeva-Gupta et al 2015). Importantly, targeting Bruton's tyrosine kinase (BTK), a key kinase for B-cell and TAM function, suppresses tumor progression in an orthotopic PDAC mouse model through the induction of TILs (Gunderson et al 2015).…”
Section: Prospect Of Pdac Immunotherapymentioning
confidence: 99%
“…In addition, stroma-derived Cxcl13 has been shown to induce the infiltration of B-cell subpopulations and promote tumor growth, likely through programming TAMs toward an M2 phenotype (Gunderson et al 2015;Lee et al 2015;Pylayeva-Gupta et al 2015). Importantly, targeting Bruton's tyrosine kinase (BTK), a key kinase for B-cell and TAM function, suppresses tumor progression in an orthotopic PDAC mouse model through the induction of TILs (Gunderson et al 2015). These preclinical data strongly support the ongoing clinical trials combining inhibitors of BTK and checkpoint blockade.…”
Section: Prospect Of Pdac Immunotherapymentioning
confidence: 99%
“…L'immunothérapie est un bon candidat, mais aucune approche de ce type n'est encore disponible pour traiter les cancers du pancréas, ce qui incite à mieux comprendre le rôle du système immunitaire dans ces tumeurs. Or, récemment, trois études ont mis en évidence des infiltrats de lymphocytes B dans l'adénocarcinome canalaire pancréatique par marquage immunohistologique de tumeurs et analyse de banques de données de transcriptome de tumeurs [4][5][6]. Dans chacune de ces études, les chercheurs identifient un mécanisme par lequel ces lymphocytes B pourraient exercer une action facilitant le dévelop-pement tumoral.…”
Section: Liens D'intérêtunclassified